Obstructive sleep apnea (OSA): healthcare and social costs - De Benedetto, Michele; Garbarino, Sergio; Sanna, Antonio (La Medicina del Lavoro, 2017)
Obstructive sleep apnea (OSA) syndrome is an underdiagnosed widespread chronic disease involving both sexes and all ages. Undiagnosed and untreated OSA is associated with workplace productivity losses and significant direct and indirect medical costs. A cost analysis of OSA was carried out in Italy ten years ago. Overall OSA medical costs, largely due to treatment of comorbidity, amounted to € 2,9 billion or 55% of total medical costs. Direct medical costs, due to diagnosis and treatment of OSA, were 6% of overall OSA costs, while medical costs due to the absence of diagnosis and of prevention of comorbidities represented 49% of the overall cost. Non-medical costs made up for the remaining 45%. € 1.5 billion could be saved by promoting screening campaigns aimed at detecting OSA that would otherwise remain undiagnosed and by improving adherence to treatment. Bearing in mind the increasing OSA prevalence and the recent quantification of avoidable OSA-related road accidents, the real cost of OSA is higher than estimated up to now.